Cut from the same cloth? Comparing Neanderthal processing of faunal resources at Amud and Kebara caves (Israel) through cut-marks analyses - Jallon, Anaëlle; Crété, Lucile; Bello, Silvia M.; Hovers, Erella; Rabinovich, Rivka (Frontiers in Environmental Archaeology, 2025)
Amud and Kebara caves (northern Israel) are two broadly contemporaneous Middle Paleolithic sites dated to ca. 70–50 Ka BP, both located in the Mediterranean realm of the southern Levant. Neanderthal occupations at these sites are represented by considerable amounts of lithic artifacts, combustion features and abundant faunal material as well as human remains. As similar mammalian taxonomic distributions were observed in these two Neanderthal cave sites, we explore the complexity and diversity of their animal resources processing techniques by comparing cut-marks characteristics and patterns. A total of 344 animal bone fragments bearing cut-marks were selected from specific stratigraphic contexts from both sites, and studied using macroscopic and microscopic techniques (i.e., Focus Variation microscopy) to quantify, characterize, and measure the cut-marks left on the bones. The observations were compared across the stratigraphic units and between the sites. Despite comparable taxonomic distributions, there are notable differences in the density and layout of cut-marks between the two caves. The micro-morphometric characteristics of these marks also highlight intra- and inter-site differences and similarities. This evidence might suggest distinctive butchering strategies between the Neanderthal populations in Amud and Kebara caves despite comparable occupation intensities, similar lithic technologies, and access to similar food resources. Such discrepancies could possibly reflect inter-group cultural differences related to carcass processing preferences, organization of tasks within the group, or socially transmitted traditions.